GO-coated P-g-C3N4 composite material containing AgNPs and preparation method thereof

By constructing a GO@P-g-C3N4 composite material containing AgNPs, using its two-dimensional/two-dimensional heterostructure, the problem of low visible light absorption rate and rapid recombination of photogenerated electron holes is solved, and photocatalysis is improved Activity and stability achieve more efficient photocatalytic effects.

CN119259097APending Publication Date: 2025-01-07苏州明能新材料科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411384842.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Graphite phase carbon nitride (g-C3N4) has low absorption rate of visible light and is easy to recombinate photogenerated electrons and holes, resulting in poor photocatalytic efficiency when used alone.

Method used

Using GO@P-g-C3N4 composite material containing AgNPs, the composite material with excellent coupling interface is formed by constructing a two-dimensional/two-dimensional heterostructure, and the electrostatic attraction between graphene oxide and protonated graphite phase carbon nitride is used. Extend light absorption and inhibit light-induced electron and hole recombination.

Benefits of technology

It improves photocatalytic activity and stability, enhances the efficiency of the photocatalyst, reduces agglomeration and photocorrosion, and promotes charge transfer and carrier separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259097A_ABST
    Figure CN119259097A_ABST
Patent Text Reader

Abstract

The invention discloses a GO-coated P-g-C3N4 composite material containing AgNPs and a preparation method of the GO-coated P-g-C3N4 composite material. The preparation method comprises the following steps: preparing a graphene oxide solution, preparing a graphene oxide nano-silver composite solution, preparing protonated graphite phase carbon nitride, and preparing the GO-coated P-g-C3N4 composite material containing AgNPs. According to the GO coated P-g-C3N4 composite material containing the AgNPs, disclosed by the invention, the defects of g-C3N4 are overcome. The two-dimensional / two-dimensional (2D / 2D) heterostructure can promote charge transfer and form an excellent coupling interface due to inherent resistance, a short transmission path, a large surface area and tight contact, so that photon-generated carriers are easier to separate. In addition, the structure exposes abundant reaction sites, the photocatalytic activity is improved, agglomeration and photocorrosion phenomena are reduced, and the efficiency and stability of the photocatalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and particularly relates to a GO@Pg-C3N4 composite material containing AgNPs and a preparation method thereof. Background Art

[0002] With the rapid development of global industrialization, energy crisis and environmental pollution have become the primary issues restricting sustainable development. Among them, water and soil pollution caused by harmful bacteria, death of animals and plants, and damage to living facilities have caused serious environmental pollution. It is extremely important to develop safe, environmentally friendly and efficient antibacterial agents.

[0003] Graphitic carbon nitride (g-C3N4) is a new type of two-dimensional photocatalytic material composed of carbon and nitrogen in the form of sp 2 Hybridization forms a π-conjugated plane, with a graphite-like structure and 3-s-triazine structural units, a narrow band gap (about 2.7 eV), and the advantages of low cost, good stability, and eco-friendliness. It has been widely used in the fields of photocatalytic degradation of organic pollutants, antibacterial, and photocatalytic hydrogen production. However, g-C3N4 has low visible light absorption and low photogenerated e- / h + Due to the easy and rapid recombination, the photocatalytic efficiency of g-C3N4 alone is not ideal. Summary of the invention

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a GO@Pg-C3N4 composite material containing AgNPs, comprising the following steps:

[0005] Step 1, preparing a graphene oxide solution, mixing concentrated H2SO4 and concentrated H3PO4 according to a certain volume ratio, adding a certain amount of graphite powder in batches, stirring, and then slowly adding a certain amount of KMnO4 in batches; continuing to heat and stir to mix, cooling to room temperature, adding a certain amount of ice water to mix, and then adding a certain amount of H2O2 drop by drop until no bubbles are generated and the solution is bright yellow; centrifuging the product, retaining the precipitate in the lower layer, centrifugally pickling it with dilute hydrochloric acid for multiple times, and then washing it with deionized water until the solution is neutral to obtain graphene oxide colloid; diluting the graphene oxide colloid with deionized water, stirring for a period of time, and obtaining a graphene oxide solution;

[0006] Step 2, preparation of graphene oxide nanosilver composite solution, mixing a certain amount of graphene oxide solution and a certain amount of AgNO3 solution, heating in a boiling water bath and then ultrasonically treating for a period of time, finally adding a certain amount of citric acid, stirring well, and standing for a period of time to obtain a graphene oxide nanosilver composite solution;

[0007] Step 3, preparation of protonized graphite phase carbon nitride, weighing an appropriate amount of urea and placing it in a tubular furnace, heating it to 550°C, keeping it warm for a period of time and then cooling it to room temperature to obtain yellow block g-C3N4; grinding the yellow block g-C3N4 into powder, taking a certain amount of g-C3N4 powder and dispersing it in concentrated hydrochloric acid, ultrasonically exfoliating it at room temperature for a period of time, and continuously stirring it, and washing it with deionized water by centrifugation until the pH value is 7.0 to obtain protonized graphite phase carbon nitride dispersed in water;

[0008] Step 4: Preparation of GO@Pg-C3N4 composite material containing AgNPs. The protonated graphite phase carbon nitride dispersed in water is added dropwise to the graphene oxide nanosilver composite solution. After stirring for a period of time, a flocculent precipitate is generated. The precipitate is freeze-dried, and the dry powder obtained is the GO@Pg-C3N4 composite material containing AgNPs.

[0009] As a preferred embodiment of the above technical solution, in step 1, the volume ratio of concentrated H2SO4 and concentrated H3PO4 is 9:1, the concentration of concentrated H2SO4 is 98%, the concentration of concentrated H3PO4 is 85%, and concentrated H2SO4 and concentrated H3PO4 are mixed to form a 200mL mixed solution, and then 2g of graphite powder is added. After stirring for 30min, 12g of KMnO4; after continuous heating for 12 hours, quickly mix in a 50°C water bath, after the water bath temperature drops to room temperature, add 400mL of ice water, and add 20mL of H2O2 dropwise until no bubbles are generated and the solution is bright yellow; centrifuge the product, remove the upper clear liquid, retain the lower precipitate, centrifuge and pickle three times with 10% by mass dilute hydrochloric acid, and then wash with deionized water until the solution is neutral to obtain graphene oxide colloid; dilute the prepared graphene oxide colloid with deionized water, put it into an ultrasonic stirring instrument, and after treating for 35 minutes, obtain a graphene oxide solution with a concentration of 0.1 mg / ml.

[0010] As a preferred embodiment of the above technical solution, in the step 2, 50 mL of graphene oxide solution and 100 mL of AgNO3 solution with a concentration of 0.05 mg / mL are mixed, heated in a boiling water bath and ultrasonically treated in an ultrasonic cleaner for 20 min, and finally 8 mg of citric acid is quickly added, stirred thoroughly and allowed to stand for 6 h to obtain a graphene oxide nanosilver composite solution.

[0011] As a preferred embodiment of the above technical solution, in step 3, the tube furnace is heated at 2°C·min -1 The mixture was heated to 550°C at a heating rate of 100 °C and kept warm for 2 h. 1 g of g-C3N4 powder was dispersed in 30 mL of concentrated hydrochloric acid, ultrasonically exfoliated at room temperature for 8 h, and stirred continuously for 16 h. The mixture was washed by centrifugation with deionized water until the pH value was 7.0 to obtain protonated graphite phase carbon nitride dispersed in water.

[0012] As a preferred embodiment of the above technical solution, in the step 4, 30 mL of protonated graphite phase carbon nitride dispersed in water is added dropwise to 8 mL of graphene oxide nanosilver composite solution, and a flocculent precipitate is generated after stirring for 3 hours.

[0013] The GO@Pg-C3N4 composite material containing AgNPs is prepared by the above preparation method.

[0014] Application of GO@Pg-C3N4 composites containing AgNPs, Application of GO@Pg-C3N4 composites containing AgNPs as antibacterial materials.

[0015] The beneficial effects of the present invention are as follows: the GO@Pg-C3N4 composite material containing AgNPs of the present invention overcomes the shortcomings of g-C3N4. It is very effective to achieve the effect of prolonging light absorption and inhibiting light-induced electron and hole recombination by constructing a heterojunction. The two-dimensional / two-dimensional (2D / 2D) heterostructure can promote charge transfer and form an excellent coupling interface due to its inherent resistance and shorter transmission path as well as large surface area and close contact, making it easier to separate photogenerated carriers. In addition, this structure exposes abundant reaction sites, improves photocatalytic activity, and helps to reduce agglomeration and photocorrosion, thereby improving the efficiency and stability of the photocatalyst. 2D carbon material graphene oxide (GO) is an important derivative of graphene and also contains aromatic (sp 2 ) and aliphatic (sp 3 ) domain, has good hydrophilicity and dispersibility, as well as a large contact area, and can act as an electron acceptor to improve the light collection efficiency and the separation efficiency of e- / h+ pairs. GO and other semiconductor composites are better than single semiconductors, forming a special van der Waals heterojunction, which can increase the photocatalytic activity of the composite material. Utilizing the electrostatic attraction between positively charged Pg-C3N4 and negatively charged graphene oxide, a GO@Pg-C3N4 composite material with a 2D / 2D heterostructure can be prepared by electrostatic self-assembly. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a SEM schematic diagram of the GO@Pg-C3N4-80% composite material containing AgNPs;

[0017] Figure 2 is the XRD pattern of GO@Pg-C3N4 composites with different mass ratios containing AgNPs;

[0018] Figure 3 This is a comparison chart of the photocatalytic inhibition rate of the control group and different photocatalysts on E.coli and S.aureus;

[0019] Figure 4 This is a comparison of the photocatalytic inhibition rates of GO@Pg-C3N4 containing different mass ratios of AgNPs against E.coli and S.aureus. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] 180 ml of 98% concentrated H2SO4 and 20 ml of 85% concentrated H3PO4 were mixed, 2 g of graphite powder was added, and after stirring for 30 minutes, 12 g of KMnO4 was slowly added in batches; after continuous heating for 12 hours, the mixture was quickly mixed in a 50°C water bath, and after the water bath temperature dropped to room temperature, 400 ml of ice water was added, and 20 ml of H2O2 was added dropwise until no bubbles were generated and the solution was bright yellow; the product was centrifuged to remove the upper clear liquid, retain the lower precipitate, and centrifugally acid washed three times with 10% mass fraction dilute hydrochloric acid, and then washed with deionized water until the solution was neutral to obtain graphene oxide colloid; the prepared graphene oxide colloid was diluted with deionized water, placed in an ultrasonic stirring instrument, and treated for 35 minutes to obtain a graphene oxide solution with a concentration of 0.1 mg / ml.

[0023] 50 mL of graphene oxide solution and 100 mL of AgNO3 solution with a concentration of 0.05 mg / mL were mixed, heated in a boiling water bath and ultrasonically treated in an ultrasonic cleaner for 20 min, and finally 8 mg of citric acid was quickly added, stirred thoroughly and allowed to stand for 6 h to obtain a graphene oxide nanosilver composite solution.

[0024] Weigh an appropriate amount of urea and place it in a tube furnace at 2°C·min -1 The mixture was heated to 550°C at a heating rate of 100 °C and kept warm for 2 h to obtain yellow block g-C3N4; the yellow block g-C3N4 was ground into powder, 1 g of the g-C3N4 powder was dispersed in 30 mL of concentrated hydrochloric acid, ultrasonically stripped at room temperature for 8 h, and continuously stirred for 16 h, and washed by centrifugation with deionized water to a pH value of 7.0 to obtain protonated graphite phase carbon nitride dispersed in water.

[0025] 30 mL of protonated graphite phase carbon nitride dispersed in water was added dropwise to 8 mL of graphene oxide nanosilver composite solution. After stirring for 3 h, a flocculent precipitate was generated, which was freeze-dried. The final dry powder obtained was the GO@Pg-C3N4-80% composite material containing AgNPs (where -80% represents that the mass fraction of Pg-C3N4 in the composite material is 80%).

[0026] Example 2

[0027] The other steps are the same as those in Example 1, except for the content of Pg-C3N4 in the composite material, and finally a GO@Pg-C3N4-70% composite material containing AgNPs is obtained.

[0028] To investigate the effect of GO@Pg-C3N4 composite materials containing AgNPs on the photocatalytic antibacterial properties, a xenon lamp (250W, output wavelength 290-800nm) was used as the light source, and blank group, control group and experimental group (illumination 150min) experiments were carried out.

[0029] Figure 3 The photocatalytic inhibition rates of the control group and each embodiment on E. coli and Staphylococcus aureus S. aureus, after 150 minutes of illumination, the inhibition rates of GO, Pg-C3N4 and GO@Pg-C3N4-80% containing AgNPs on E. coli and S. aureus were 63.56%, 92.88%, 99.97% and 72.63%, 85.96%, 99.95% respectively. Under dark conditions, GO@Pg-C3N4-80% containing AgNPs has a certain bactericidal ability, because GO@Pg-C3N4-80% containing AgNPs is a 2D material with sharp edges that can directly physically pierce or cut bacteria like a knife, resulting in cell dysfunction and leakage of cytoplasmic components and inactivation. After 150 minutes of illumination, the number of colonies of GO@Pg-C3N4-80% containing AgNPs was significantly reduced compared with GO and Pg-C3N4. Analysis of the reasons: On the one hand, GO@Pg-C3N4-80% containing AgNPs can inactivate bacteria through sharp edges, and on the other hand, it can reduce the recombination rate of electrons and holes during photocatalysis, allowing more electrons and holes to react with O2 and H2O to generate reactive oxygen species ROS, oxidize unsaturated phospholipid molecules into lipid peroxides, and interfere with normal cell metabolism, thereby achieving excellent antibacterial effects.

[0030] Figure 4The effect of the mass ratio of composite materials containing AgNPs on the photocatalytic antibacterial performance was investigated. GO@Pg-C3N4-70%, GO@Pg-C3N4-80%, and GO@Pg-C3N4-90% were used as photocatalysts, and a xenon lamp was used as the light source. The illumination was performed for 150 minutes. The results are shown in FIG. Figure 4 As shown. Figure 4 It can be seen that after 150 minutes of illumination, the antibacterial rates of GO@Pg-C3N4-70% against E.coli and S.aureus were 98.78% and 98.61%, respectively. As the content of Pg-C3N4 in the composite material continued to increase, the antibacterial rate increased accordingly. The antibacterial rates of GO@Pg-C3N4-80% against E.coli and S.aureus reached more than 99.90%, and the antibacterial rate tended to be flat as the content of Pg-C3N4 continued to increase.

[0031] It is worth mentioning that the technical features such as the tubular furnace and ultrasonic cleaner involved in the patent application of this invention should be regarded as the prior art. The specific structure, working principle and possible control method and spatial layout method of these technical features can be selected according to the conventional methods in the field, and should not be regarded as the inventive point of this patent. This patent will not be further elaborated.

[0032] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the existing technology should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a GO@Pg-C3N4 composite material containing AgNPs, characterized in that: The following steps are included: Step 1, preparing a graphene oxide solution, mixing concentrated H2SO4 and concentrated H3PO4 according to a certain volume ratio, adding a certain amount of graphite powder in batches, stirring, and then slowly adding a certain amount of KMnO4 in batches; continuing to heat and stir to mix, cooling to room temperature, adding a certain amount of ice water to mix, and then adding a certain amount of H2O2 drop by drop until no bubbles are generated and the solution is bright yellow; centrifuging the product, retaining the precipitate in the lower layer, centrifugally pickling it with dilute hydrochloric acid for multiple times, and then washing it with deionized water until the solution is neutral to obtain graphene oxide colloid; diluting the graphene oxide colloid with deionized water, stirring for a period of time, and obtaining a graphene oxide solution; Step 2, preparation of graphene oxide nanosilver composite solution, mixing a certain amount of graphene oxide solution and a certain amount of AgNO3 solution, heating in a boiling water bath and then ultrasonically treating for a period of time, finally adding a certain amount of citric acid, stirring well, and standing for a period of time to obtain a graphene oxide nanosilver composite solution; Step 3, preparation of protonized graphite phase carbon nitride, weighing an appropriate amount of urea and placing it in a tubular furnace, heating it to 550°C, keeping it warm for a period of time and then cooling it to room temperature to obtain yellow block g-C3N4; grinding the yellow block g-C3N4 into powder, taking a certain amount of g-C3N4 powder and dispersing it in concentrated hydrochloric acid, ultrasonically exfoliating it at room temperature for a period of time, and continuously stirring it, and washing it with deionized water by centrifugation until the pH value is 7.0 to obtain protonized graphite phase carbon nitride dispersed in water; Step 4: Preparation of GO@Pg-C3N4 composite material containing AgNPs. The protonated graphite phase carbon nitride dispersed in water is added dropwise to the graphene oxide nanosilver composite solution. After stirring for a period of time, a flocculent precipitate is generated. The precipitate is freeze-dried, and the dry powder obtained is the GO@Pg-C3N4 composite material containing AgNPs.

2. The method for preparing the GO@Pg-C3N4 composite material containing AgNPs according to claim 1, characterized in that: In the step 1, the volume ratio of concentrated H2SO4 and concentrated H3PO4 is 9:1, the concentration of concentrated H2SO4 is 98%, and the concentration of concentrated H3PO4 is 85%. Concentrated H2SO4 and concentrated H3PO4 are mixed to form a 200mL mixed solution, and then 2g of graphite powder is added. After stirring for 30min, 12g of KMnO4; after continuous heating for 12 hours, quickly mix in a 50°C water bath, after the water bath temperature drops to room temperature, add 400mL of ice water, and add 20mL of H2O2 dropwise until no bubbles are generated and the solution is bright yellow; centrifuge the product, remove the upper clear liquid, retain the lower precipitate, centrifuge and pickle three times with 10% by mass dilute hydrochloric acid, and then wash with deionized water until the solution is neutral to obtain graphene oxide colloid; dilute the prepared graphene oxide colloid with deionized water, put it into an ultrasonic stirring instrument, and after treating for 35 minutes, obtain a graphene oxide solution with a concentration of 0.1 mg / ml.

3. The method for preparing the GO@Pg-C3N4 composite material containing AgNPs according to claim 1, characterized in that: In the step 2, 50 mL of the graphene oxide solution and 100 mL of a 0.05 mg / mL AgNO3 solution are mixed, heated in a boiling water bath and ultrasonically treated in an ultrasonic cleaner for 20 min, and finally 8 mg of citric acid is quickly added, stirred thoroughly and allowed to stand for 6 h to obtain a graphene oxide nanosilver composite solution.

4. The method for preparing the GO@Pg-C3N4 composite material containing AgNPs according to claim 1, characterized in that: In step 3, the tube furnace is heated at 2°C min -1 The mixture was heated to 550°C at a heating rate of 100 °C and kept warm for 2 h. 1 g of g-C3N4 powder was dispersed in 30 mL of concentrated hydrochloric acid, ultrasonically exfoliated at room temperature for 8 h, and stirred continuously for 16 h. The mixture was washed by centrifugation with deionized water until the pH value was 7.0 to obtain protonated graphite phase carbon nitride dispersed in water.

5. The method for preparing the GO@Pg-C3N4 composite material containing AgNPs according to claim 1, characterized in that: In the step 4, 30 mL of protonated graphite phase carbon nitride dispersed in water was added dropwise to 8 mL of graphene oxide nanosilver composite solution, and stirred for 3 hours to generate flocculent precipitate.

6. A GO@Pg-C3N4 composite material containing AgNPs, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

7. Application of GO@Pg-C3N4 composite material containing AgNPs, characterized in that: Application of GO@Pg-C3N4 composites containing AgNPs as antibacterial materials.

Citation Information

Patent Citations

  • Silver / graphene oxide / carbon nitride composite photocatalytic material and preparation method thereof

    CN104437589A

  • Method for preparing efficient bactericide silver / graphite phase carbon nitride composite material

    CN105664991A

  • Preparation method of graphene oxide-nano silver material with good antibacterial performance

    CN107915221A

  • Preparation method of Ag / GO photocatalytic material for sterilization

    CN110201667A